Validating the Force Concept Inventory with Sub-Questions: Preliminary Results of the Second Year Survey - Yasuda, Jun-ichiro; Taniguchi, Masa-aki (Scientia in educatione, 2017)
We address the validity of the FCI, that is, whether respondents who answer FCI questions correctly have an actual understanding of the concepts of physics tested in the questions. We used sub-questions that test students on concepts believed to be required to answer the actual FCI questions. Our sample size comprises about five hundred respondents; we derive false positive ratios for pre-learners and post-learners, and evaluate the significant difference between them. Our analysis shows a significant difference at the 95 % confidence level for Q.6, Q.7, and Q.16, implying that it is possible for post-learners to answer three questions without understanding the concepts of physics tested in the questions; therefore, Q.6, Q.7 and Q.16 are invalid.